Effect of stacking pressure on the performance of polymer electrolyte membrane fuel cell with various channel types. (15th March 2021) - Son, Jonghyun; Lee, Daye; Um, Sukkee; Kim, Young-Beom
Highlights: Effect of stacking pressure on power of PEMFC with varied channel types was studied. Stacking pressure and channel type were analyzed simultaneously as variables. Serpentine, parallel, and interdigitated channels were adopted for the combined study. Result of serpentine channel case was affected most sensitively by stacking pressure. Different stacking pressure should be considered for high power PEMFC system. Abstract: Polymer electrolyte membrane fuel cell (PEMFC) stacks are assembled via the sequential stacking of a number of PEMFC unit cells. In such a process, stacking pressure is applied to the PEMFC stack. This compression pressure causes a change in mass transport and electrical conduction characteristics. In this paper, various stacking pressures were applied to three types of PEMFC unit cells with serpentine, parallel, and interdigitated cathode channels to understand the effect of stacking pressure on PEMFC performance. Numerical analyses were conducted with a validated 3-D PEMFC model. Deformation of the gas diffusion layer (GDL) by compression was not influenced by the channel type. However, the results of the electrochemical simulation showed different influence of stacking pressure depending on the operating voltage and cathode channel type. To improve PEMFC performance, it was concluded that the stacking pressure should be determined by considering the channel type and operating voltage.